Sustainable Development Indicators As A Tool For Monitoring Unfair International Market Competition Of Mineral Commodities (Society for Mining, Metallurgy & Exploration, 2003)
Although mineral commodities used to play and still play a very crucial role in the development of civilization over the centuries, their extraction, transportation, transformation and use are at present sources of great concern in terms of sustainability. Some of the most discussed environmental problems are in fact closely related to the utilization of minerals as materials and fossil fuels. The paper analyses the origins of sustain-ability weakness of mineral supply through Environmental Economics models, which have interpreted the phenomena of pollution and non-renewable resource depletion as a market failure. Conventional market tools have proved to be unable to perform an optimal allocation of those resources that are priceless or have open access. An external intervention is needed in order to reduce the excessive exploitation of environmental and natural resources. Some of the solutions proposed by policymakers and subsequently implemented by governments are briefly considered and the achieved results are discussed. In several cases the public intervention, where the attempt was to restore the sustainability conditions, has failed. Restrictive environmental protection regulations have resulted in severe limitations to the mining activity, without, on the other hand, achieving the expected results in terms of sustainability. Some of these regulations instigate unfair international competition practices among those producers who do care about the environment, but who have high production costs, and those who supply cheap raw material but whose low costs hide heavy environmental impacts. Nowadays, most of the world?s supply of minerals is being produced in developing countries, with severe global environmental impacts. As effective tools for monitoring the problem, sustainable development indicators could be used by policymakers to duly associate the comprehensive environmental impacts for each mining product, depending on its origin and extraction history.